On the nascent wind of oxygen-rich AGB stars: scrutiny of a sample of nearby stars - Darriulat, Pierre; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Diep, Pham Ngoc; Ngoc, Nguyen Bich; Thai, Tran Thi; Anh, Pham Tuan (Comptes Rendus. Physique)
The commonly accepted mechanism governing the formation of the nascent wind in oxygen-rich AGB stars combines an initial boost above the photosphere, given by shock waves resulting from stellar pulsations and convective cell partition, with a subsequent acceleration fuelled by the radiation pressure of the star on dust grains. We use six nearby stars, for which detailed studies of visible and infrared observations at the VLT and millimetre observations at ALMA are available, to assess the extent to which the validity of this picture is currently corroborated. We show that while providing a very useful guide to current research and having received general support and suffered no contradiction, it still requires many additional observations to be reliably validated. In particular, observations of the highest possible angular resolution at both millimetre and visible/infrared wavelengths, performed in conjunction with measurements of the light curve, are necessary to tell apart the respective roles played by convection and stellar pulsations. The observed concurrence of high variability near the photosphere with persistence over decades, or even centuries, of the global anisotropy displayed by the CSE needs to be understood. New observations of the close neighbourhood of the star are required to elucidate the mechanism that governs rotation, in particular in the cases of R Dor, L2 Pup and EP Aqr. We argue that the presence of stellar or planetary companions does not seriously impact the formation of the nascent wind and only modifies its subsequent evolution.